1998
DOI: 10.1042/bj3290095
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the redox state of cytochrome c during caspase activation in cytosolic extracts

Abstract: The export of cytochrome c from mitochondria to the cytoplasm has been detected during apoptosis. Addition of cytochrome c to cytosolic extracts can activate the caspases, suggesting that this export could be an important intracellular signal for initiating the apoptotic programme. We have investigated the mechanism of caspase activation by cytochrome c. Mitochondrial cytochrome c normally shuttles electrons between complexes III and IV of the electron transport chain. Interaction with these complexes is depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 14 publications
5
76
0
Order By: Relevance
“…Secondly, cyanide will be directly toxic to airway cells and, finally, cyanide may also contribute to the relative inability of neutrophils to clear P. aeruginosa infection in the CF lung [15,16]. In the concentrations reported, cyanide has been shown to inhibit the function of the enzyme myeloperoxidase and prevent production of hypochlorous acid during the oxidative burst [17]. Cyanide may also impair neutrophil migration and cause morphological changes related to damage to the cell cytoskeleton [18].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, cyanide will be directly toxic to airway cells and, finally, cyanide may also contribute to the relative inability of neutrophils to clear P. aeruginosa infection in the CF lung [15,16]. In the concentrations reported, cyanide has been shown to inhibit the function of the enzyme myeloperoxidase and prevent production of hypochlorous acid during the oxidative burst [17]. Cyanide may also impair neutrophil migration and cause morphological changes related to damage to the cell cytoskeleton [18].…”
Section: Discussionmentioning
confidence: 99%
“…We have been unable to do this due mainly to the difficulty of maintaining the injected cytochrome c in the oxidized state in vivo. Hampton et al 14 in their in vitro experiments used minimal quantities of cyanide to maintain the protein in its oxidized state to demonstrate its efficacy in activating caspases. We are currently grappling with the technical difficulties of using a similar approach in vivo.…”
Section: Membrane Potential In Xenopus Oocytes During Cell Deathmentioning
confidence: 99%
“…An in vitro model indeed indicated that either oxidation state is effective in the activation of caspases. 14 15,16 In our experiments we compared the kinetics of plasma membrane depolarization induced by oxidized cytochrome c and dithionite-reduced cytochrome c added to the cytosol by microinjection. In the time dependence of the change of DC, shown in Figure 3A, we observe a time lag of *20 min for the oxidized state of cytochrome c relative to the reduced one.…”
Section: Membrane Potential In Xenopus Oocytes During Cell Deathmentioning
confidence: 99%
“…6,13 In this manner S-100 cytosols from various cell sources can be shown to generate specific type-II caspase activity (DEVD-ase) dependent upon holoCyt-c and dATP additions. 10,14 Therefore, we choose to determine if the capacity of human skeletal muscle cytosols qualitatively paralleled the holoCyt-c/dATP-mediated activation of type-II caspases seen in haematopoietic cells. Our observations suggest that these cytosols were devoid of holoCyt-c-inducible caspase activity and that this result is indicative of a necessary endogenous mechanism for the regulation and maintainance of skeletal muscle integrity.…”
Section: Introductionmentioning
confidence: 99%